2008
DOI: 10.1063/1.3010381
|View full text |Cite
|
Sign up to set email alerts
|

High power microwave switching utilizing a waveguide spark gap

Abstract: A reduction in the rise time of a 2.85 GHz high power microwave (HPM) pulse is achieved by implementing an overvoltaged spark gap inside a waveguide structure. The spark gap is oriented such that when triggered, the major electric field component of the dominant TE(10) mode is shorted. The transition from a transmissive to a highly reflective microwave structure in a relatively short period of time (tens of nanoseconds) creates a means to switch multimegawatt power levels on a much faster timescale than mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…This does not appear to be a large factor when simulating the simpler breakdown parameters (e.g., delay time, breakdown field) but the late-pulse parameters such as maximum attenuation and the plasma density profile appear to depend heavily on these scaling laws as well as the geometry of the apparatus and the mode structure of the RF power. Therefore, in order to more closely match the experimental data measured using the complex waveguide geometry, the simulation could be expanded to include a greater number of plasma growth and loss processes; the simulation could also be scaled to 2 or 3 dimensions to allow the direct modeling of microwave interaction with the experimental geometry 14 and non-uniform plasma, reducing the number of assumptions necessary.…”
Section: Limitations Of the 1d-fdtd Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This does not appear to be a large factor when simulating the simpler breakdown parameters (e.g., delay time, breakdown field) but the late-pulse parameters such as maximum attenuation and the plasma density profile appear to depend heavily on these scaling laws as well as the geometry of the apparatus and the mode structure of the RF power. Therefore, in order to more closely match the experimental data measured using the complex waveguide geometry, the simulation could be expanded to include a greater number of plasma growth and loss processes; the simulation could also be scaled to 2 or 3 dimensions to allow the direct modeling of microwave interaction with the experimental geometry 14 and non-uniform plasma, reducing the number of assumptions necessary.…”
Section: Limitations Of the 1d-fdtd Methodsmentioning
confidence: 99%
“…Variation in measured power incident on the window is expected and observed which leads to difficulty in comparing with the presented simulation; however, the power levels at breakdown are consistent over datasets. Details of the experimental setup are explained by Foster et al 14 The experimental apparatus (shown in Fig. 2) is nontrivial to model, but the simulation described in this paper assumes only the experimental section with a source wave incident from the WR-284 waveguide side; the transmitted and reflected waves are assumed to be terminated appropriately with no reflections from the waveguide geometry.…”
Section: Methodsmentioning
confidence: 99%
“…A full description of the experimental setup can be found elsewhere. 14 Additionally, the setup utilizes a continuous wave UV xenon arc lamp to illuminate the polycarbonate window surface. A quartz window with a cutoff wavelength of 180 nm ͑quantum energy 6.9 eV͒ is used to direct the UV radiation toward the window and the cutoff of the spectral distribution of the arc emission is at 6.1 eV.…”
Section: A Nitrogenmentioning
confidence: 99%
“…Fig. 12 shows the comparison of the GM with experiments in air [29]. The power in the experiment is 3.5 MW, E 0 = 11.4 ± 0.3 kV/cm, and f = 2.85 GHz.…”
Section: Frequency Effect On Gmmentioning
confidence: 99%